National culture of secrecy and firms’ access to credit - Bertrand, Jérémie; Klein, Paul-Olivier; Pasiouras, Fotios (Journal of Banking & Finance, 2024)
High secrecy cultures are characterized by a preference for confidentiality and non-disclosure of information. This study documents the impact of cultural differences in secrecy on firms’ access to credit. We use data from the World Bank Enterprise Surveys for a large sample of firms operating in 35 countries from 2010 to 2019. We show that firms operating in countries with higher levels of secrecy are less likely to apply for credit when they need it—they are more discouraged—and also less likely to receive credit when they do apply—they are more rationed. The underlying economic channels are greater opacity and corruption in cultures with high secrecy. The effect of cultural secrecy on credit discouragement and credit rationing is moderated by trust in banks, interpersonal trust, and firms’ financial dependence on external sources. We control for several potential alternative drivers and conduct several robustness tests. The results confirm that firms have better access to credit in cultures that promote transparency and information disclosure.